PENGARUH MEDIA VISUAL DAN TUBIAN TERHADAP HASIL BELAJAR STUKTUR BAHASA JERMAN - Meutiawati, Tia (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2015)
The purpose of this quasi-experiment was to determine the effects of teaching techniqucs bv using visualmediamd dnh and ewm behwior on students' achievemcnt in learning German smrctutes.This quasi-experinagnt fourth senuster 6 wih a criterion-group daign wss conducted in fue academic yearlgg2ltggj a SMII 6 Yogyakarta.The sample t<,us divided into two groups consisting of 20 students with high and low entry behaviors respective$. The group was taugltt by using viswl wdia and tu second hy drills.Suderus' entry behwior nas determined by scores they obtaircdlrom their achievement in German hnguage at the end of the third senuster. Their achievemmt in German structures in this experimennl design tws mcasured by a strrcture test. Thc test had a validit.vr of 0,7A5 md rehability r = 0,924.Alur the experimeruu ttu 4 semcster a two-rtyty ana$sis af varianci and the iwk"v+est with a lcvel of significant alpha : 0,05 were used to test the hypotheses. Thc result indicated that:(l) There was no dffirence befiyeentlw students' achia,ement nught by using viswl media ditb; (2) For sudents with a high lcvel erury belwvior, there was no differmce in achievemews between using visual media and drilts; (3) Howarcr students with low mtr-v behavior achieved higher scores with vistul media tlwn drilb. Th,s,this research impties tha smden* with low ewry belwior the usevisual media can be helpful.